A Homozygous Mutation on the HBA1 Gene Coding for Hb Charlieu (HBA1: c.320T>C) Together with β-Thalassemia Trait Results in Severe Hemolytic Anemia. (4th March 2019) - Klei, Thomas R. L.; Kheradmand Kia, Sima; Veldthuis, Martijn; Dehbozorgian, Javad; Karimi, Mehran; Geissler, Judy; Sellink, Erica; Thiel-Valkhof, Marijke; Burger, Patrick; van Alphen, Floris; Meijer, Alexander B.; van Bruggen, Robin; et al.
Abstract: A 4-year-old boy, a β-thalassemia (β-thal) carrier, with an unexplained severe chronic microcytic anemia was referred to us. Sequencing of the α-globin genes revealed a Hb Charlieu [α106(G13)Leu→Pro, HBA1 : c.320T>C, p.Leu107Pro] mutation present on both HBA1 genes. Quantitative polymerase chain reaction (qPCR) confirmed α Charlieu mRNA in the proband and his parents, showing that the mutation does not affect mRNA stability. However, we were unable to detect the Hb Charlieu protein by capillary electrophoresis (CE), reverse phase electrophoresis, cation exchange electrophoresis or isoelectric focusing. Mass spectrometry (MS) allowed us to confirm the presence of the Hb Charlieu peptide in erythrocyte progenitors. These findings suggest that the mutation affects the stability of α Charlieu . As hemoglobin (Hb) heat stability tests showed no abnormalities in erythrocytes, we speculated that α Charlieu is already degraded during red blood cell (RBC) development. The clinical severity in the proband and the presence of new methylene blue-stained aggregates in his reticulocytes indicates that incorporation of α Charlieu destabilizes Hb. This, combined with an excess of unstable free α-globins as the result of β-thal minor, results in severely impaired erythropoiesis and, as a consequence, severe and chronic microcytic anemia in the proband.